PELAYANAN SOSIAL LANJUT USIA KOTA BANJARMASIN - Sudarsono, Muhammad; Muchamad, Bani Noor (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2020)
The Elderly Social Services is a community service institution under the auspices of the Social Service which is intended to improve the welfare of the elderly in their old age. The lack of this institution in the city of Banjarmasin has an impact on the low welfare of the elderly in the city of Banjarmasin. Designing Elderly Social Services in the city of Banjarmasin is expected to improve the welfare of the elderly in the city of Banjarmasin, to help achieve the goal of improving welfare of the elderly. The problem raised in the elderly social services is the design that requires it to be a comfortable home and gives the impression of kinship to its inhabitants. Research using behavioral architectural methods as a reference in designing, so as to produce a Homey concept in buildings to make the elderly feel comfortable and find the meaning of the word back home, in buildings that conceptualize the homey of the elderly will be directed to know each other and make a family impression between them.